Treatment-resistant schizophrenia: How far have we traveled? - Pandey, Ambu; Kalita, Kamal Narayan (Frontiers in Psychiatry, 2022)
Treatment-resistant Schizophrenia is a lack of adequate response to antipsychotic medications resulting in incomplete functional and social recovery from the illness. Different definitions have been proposed for clinical practice and research work. Antipsychotics which are used in the management of Schizophrenia mainly act on multiple dopaminergic pathways which are implicated in the development of symptoms of Schizophrenia. Newer antipsychotics also are implicated to affect the serotonergic pathways. Clozapine is the only evidence based treatment available for the management of treatment-resistant cases. Neurobiologically there is a considerable overlap between treatment-resistant and treatment-responsive cases. The factors that are implicated in evolution of treatment resistance is still not conclusive. These make the management of such patients a challenge. However certain peculiarities of treatment-resistant Schizophrenia have been identified which can guide us in early identification and precise treatment of the treatment-resistant cases.